Implementation of the Ummi Method to Improve the Al-Qur'an Reading Skills of Students at Sd IT Bakti 2 Nairatul Jannah Padang - Abddul Hakim Pohan; Martin Kustati; Nana Sepriyanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The Ummi method is a method that teaches reading the Koran properly and correctly. The purpose of writing this article is to describe the application of the Ummi method and find out the obstacles that arise in learning the Koran at SD IT Bakti 2 Nairatul Jannah. The conclusion results show that the implementation of the Ummi method of learning the Koran in the school is carried out through seven learning stages and the superiority of the Ummi method lies in the 10 pillars of the quality system. The obstacle found was that 2 out of 3 teachers had not been certified with the Ummi method. This has an impact on the learning process where there are still errors in reading and memorizing the Koran because the stages of instilling and understanding concepts have not been mastered by the teacher. Apart from that, it is felt that the Alquraan coordinator as the school principal is very busy with school administration matters, so internal control is still very lacking.